Strategi Pemasaran Produk UMKM Rattan Sintetis Melalui Digital Marketing di Desa Karangmulya Kabupaten Cirebon - Dian Fitriyana; Annisaa Eka Warliati; Tia Listiaty (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2022)
This study aims to analyze the marketing strategies that affect the success of MSME businesses in Cirebon. The marketing strategy that will be developed is a synthetic rattan marketing strategy which is still not developed in marketing. This condition stems from marketing that still uses offline media as its target market. Researchers will develop marketing strategies with online methods, both through social media such as Instagram, YouTube and e-commerce. The method used in this activity is descriptive qualitative research. The research subjects in this study were informants who provided research data through interviews and purposive sampling techniques. Based on the results of qualitative research using interview and observation techniques and the data that the authors have collected, it can be concluded that digital marketing has a very large influence on product marketing because it can increase sales volume and also increase profits for MSME entrepreneurs. Business success can be achieved with the efforts of various parties, both external and internal. One of the external efforts made by the government is to develop the MSME sector in collaboration with academics and MSME business actors.